100 Best Bikes - Sardar, Zahid (London : Laurence King Publishing Ltd, 2012)
These are the best bikes to be found anywhere right now, giving every kind of cyclist an overview of what is out there. Whether a BMXtreme or mountain bike enthusiast, a keen tourer or racer, a city commuter or courier, or simply fascinated with the constantly advancing mechanics and engineering of folding and other innovative bike designs, this book has something for you. The bikes on display come from across Europe, East and South Asia and North America, not to mention examples from the southern hemisphere. The major bike manufacturers like Boardman, Giant and Fuji are of course featured, but also more maverick material from Biomega, Calfee and Daymak. 100 Best Bikes is the essential resource for anyone wanting toknow about the best in design and engineering for every kind of bike
Keywords: Bicycles and bicycling; Bicycles -- Design and construction